A Curvelet-Based Morphological Segmentation of Abdominal CT Images - (:unkn) unknown (IEEE, 2014)
This paper presents a segmentation methodology of abdominal axial CT images. The aim of the study is to determine the location of mesenteric area from the axial images so the organs enclosed within can be localized precisely for diagnostic purposes. The challenge confronted here is that there is no a certain deterministic shape of abdominal organs. The methodology implemented here utilizes a curvelets stage followed by morphological image processing to achieve a contour emphasized segmentation from the gestalts of surrounding organs. This paper gives a detailed analysis of approach taken with the problems faced and a brief comparison wrt to other wavelet approaches.
Keywords: curvelets; wavelets; abdominal image segmentation; non-maximal suppression; edge and contour detection; non-maximal suppression; connected-components labeling; COMPRESSION; TRANSFORMS